T-cell-independent resistance to infection and generation of immunity to Francisella tularensis. - Elkins, K L (1993)
The intraperitoneal 50% lethal dose (LD50) for Francisella tularensis LVS in both normal control heterozygote BALB/c nu/+ mice and BALB/c nu/nu mice was 2 x 10(0). Both nu/+ and nu/nu mice given 10(7) LVS bacteria or more intradermally (i.d.) died, with a mean time to death of about 7 to 8 days. On the other hand, nu/+ mice given 10(6) LVS bacteria or less survived for more than 60 days and cleared systemic bacteria, while nu/nu mice given 10(6) LVS bacteria or less survived for more than 10 days but died between days 25 and 30. Thus, the short-term (i.e., < 10-day) i.d. LD50 of both nu/nu and nu/+ mice was 3 x 10(6), but the long-term (i.e., > 10-day) i.d. LD50 of nu/nu mice was less than 7 x 10(0). The short-term survival of i.d. infection was dependent on tumor necrosis factor and gamma interferon: treatment of nu/nu mice with anti-tumor necrosis factor or anti-gamma interferon at the time of i.d. infection resulted in death from infection 7 to 8 days later, whereas control infected nu/nu mice survived for 26 days. nu/nu mice infected with LVS i.d. generated LVS-specific serum antibodies, which were predominantly immunoglobulin M: titers peaked 7 days after i.d. infection but declined sharply by day 21, after which mice died. Surprisingly, nu/nu mice given 10(3) LVS bacteria i.d. became resistant to a lethal challenge (5,000 LD50s) of LVS intraperitoneally within 2 days after i.d. infection; nu/nu mice similarly infected with LVS i.d. and challenged with Salmonella typhimurium (10 LD50s) were not protected. nu/nu mice given nu/+ spleen cells intravenously as a source of mature T cells survived i.d. infection for more than 60 days and cleared bacteria. Taken together, these studies demonstrate that i.d. infection of nu/nu mice with LVS rapidly generates T-cell-independent, short-term, specific protective immunity against lethal challenge, but T lymphocytes are essential for long-term survival.